Changes in activity and structure of lysosomes from liver of mouse irradiated in vivo. (2nd April 2018) - Wieczorek, Anna; Lysek-Gladysinska, Malgorzata; Walaszczyk, Anna; Jelonek, Karol; Smolarz, Mateusz; Pietrowska, Monika; Gabrys, Dorota; Kulik, Roland; Widlak, Piotr
Abstract: Purpose: Lysosomes may have an important role in response to ionizing radiation. Moreover, radiation could affect autophagy, which process involves the activity of lysosomal enzymes. In the present study, the effect of ionizing radiation on the lysosomal compartment of mouse liver was investigated after in vivo exposure. Materials and methods: Morphology and ultrastructure of hepatocytes were assessed by light and electron microscopy, and activities of selected lysosomal enzymes were assessed in 12, 36 and 120 h after exposure to the mean dose of 1 Gy. The levels of autophagy-related proteins LC3-II and p62 were compared by Western blotting between untreated and irradiated animals (120 h after exposure). Results: Increased number of autophagic vacuoles in hepatocytes from exposed animals was documented in the ultrastructural study; destroyed mitochondria were the dominant component of such vacuoles. Moreover, an increased activity of lysosomal hydrolases was observed after exposure. However, levels of autophagy substrates LC3-II and p62 were barely affected in exposed animals 120 h after irradiation when the accumulation of autophagic vacuoles was observed. Conclusion: Effects of irradiation included an increased number of autophagic vacuoles, especially of autophagosomes, and increased activity of lysosomal enzymes. However, putative markers of autophagic flux were not observed, which suggested suppression of the completion of the radiation-mediated autophagy pathway.